ChemInform Abstract: Asymmetric Organocatalytic Mannich Reaction of 1‐Aryl‐2, 2, 2‐trifluoroethylidenecarbamic Acid Derivatives with Acetone. Issue 7 (22nd February 2013) - Golovach, N. M.; Tkachuk, V. N.; Sukach, V. A.; Vovk, M. V.
Abstract Carbamates (I) and ureas (IV) undergo asymmetric Mannich reactions with acetone (II) to give optically active compounds (III) or (V), resp., and, by intramolecular cyclization of the latter, dihydropyrimidinones (VI).